Corporate governance and firm value : the Singapore evidence - Ho, Joyce Huay Seann (2008)
We examine the valuation impact with the level of diversification as well as various corporate governance variables on publicly listed Singapore companies in the year 1995/1996. Our key findings include higher firm value for diversified firms, specifically for publicly owned firms and monitoring role of blockholders in GLCs of Singapore.